2015
DOI: 10.1007/s11136-015-1069-5
|View full text |Cite
|
Sign up to set email alerts
|

Development of an item bank for computerized adaptive test (CAT) measurement of pain

Abstract: Abstract:Background: Patient-reported outcomes should ideally be adapted to the individual patient while maintaining comparability of scores across patients. This is achievable using computerized adaptive testing (CAT). The aim here was to develop an item bank for CAT measurement of the pain domain as measured by the EORTC QLQ-C30 questionnaire. Methods: The development process consisted of four steps. 1) Literature search. 2) Formulation of new items. 3) Pre-testing. 4) Field-testing and psychometric analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…In agreement with findings of the current study, several studies reported no significant association between severity of dementia and caregivers' depression [ 24 , 25 ]. Välimäki et al [ 26 ] explained the insignificant correlation between the AD patients' disease severity and their caregivers' degree of depression by the fact that caregivers of patients with dementia are already at the lowest level of health-related quality of life compared with the general population.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with findings of the current study, several studies reported no significant association between severity of dementia and caregivers' depression [ 24 , 25 ]. Välimäki et al [ 26 ] explained the insignificant correlation between the AD patients' disease severity and their caregivers' degree of depression by the fact that caregivers of patients with dementia are already at the lowest level of health-related quality of life compared with the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic illness experiences are also threaded through with characteristics of temporality (Jowsey 2015), including permanency, permeation, and fluctuation. Chronic illness is permanent, meaning it endures long-term and often forecasts a trajectory of health decline.…”
Section: Space Time Chronic Illness and Leisurementioning
confidence: 99%
“…Health status might also shape a person’s leisure-scape in terms of where, when, and how they can enjoy leisure given the unique spatial and temporal characteristics of chronic illness symptoms and management (Jowsey 2015, Crooks 2007). Chronic kidney disease (CKD), a term used to describe loss of kidney function over time, for example, can fundamentally restructure a person’s life.…”
Section: Introductionmentioning
confidence: 99%
“…With enhanced computer technology, screening questions can lead to a battery of more detailed measures as indicated by the patients' initial responses. Computer-adaptive test [43,44] allows for adaptation of the questionnaire to the individual patient, thereby minimizing questionnaire burden yet optimizing measurement precision and achieving a more detailed level of HR-QoL outcomes. Wider use of mathematical modeling such as Rasch analysis will serve to underpin refinements in questionnaires and the data outputs.…”
Section: Five-year Viewmentioning
confidence: 99%